2011
DOI: 10.1371/journal.pone.0028813
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects of Pravastatin and Simvastatin on the Growth of Tumor Cells from Different Organ Sites

Abstract: 3-hydroxy-3-methylglutaryl coenzyme A reductase (HMGCR) inhibitors, commonly known as statins, may possess cancer preventive and therapeutic properties. Statins are effective suppressors of cholesterol synthesis with a well-established risk-benefit ratio in cardiovascular disease prevention. Mechanistically, targeting HMGCR activity primarily influences cholesterol biosynthesis and prenylation of signaling proteins. Pravastatin is a hydrophilic statin that is selectively taken up by a sodium-independent organi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
74
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(78 citation statements)
references
References 59 publications
3
74
0
1
Order By: Relevance
“…Aln is a farnesyl pyrophosphate synthase inhibitor and Sv is an HMG CoA reductase inhibitor. The combination of both drugs can effectively inhibit the mevalonate cascade and the generation of downstream isoprenoids and geranylgeranylation of proteins [23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aln is a farnesyl pyrophosphate synthase inhibitor and Sv is an HMG CoA reductase inhibitor. The combination of both drugs can effectively inhibit the mevalonate cascade and the generation of downstream isoprenoids and geranylgeranylation of proteins [23].…”
Section: Discussionmentioning
confidence: 99%
“…There is increasing evidence that BPs also directly inhibit cancer cells by acting either on tumour cell proliferation/survival or by having an anti-angiogenic potential [22]. Many in vitro studies have established the antiproliferative effects of pamidronate or Aln on different cancer cells, such as osteosarcoma, breast, myeloma, and melanoma and recently on neuroblastoma cancer cells [23].…”
Section: Discussionmentioning
confidence: 99%
“…The existence of differential effects between hydrophobic statins such as simvastatin and hydrophilic statins such as pravastatin have been proposed, as simvastatin appears to produce greater antitumor effects compared with pravastatin in several cancer cell lines (excluding pancreatic) in vitro (69). However, another study demonstrated that, although simvastatin produced the greatest antitumor effects in vitro, rosuvastatin, cerivastatin and fluvastatin had the most potent antitumor effects in animal models of PDAC at the recommended human doses, with all statins (hydrophobic and hydrophilic) except pravastatin exerting inhibitory effects on intracellular Ras translocation (70).…”
Section: Mechanisms Of Action and Evidence Of Antitumor Effects Of Stmentioning
confidence: 99%
“…Poorly-differentiated cancer cells were generally more responsive to simvastatin than well-differentiated cancer cells, and the levels of HMG-CoA reductase expression did not consistently correlate with response to statin treatment. Hydrophilic drug pravastatin was ineffective in inhibiting the growth or altering the biologic behavior of selected tumor cell lines (Menter et al 2011).…”
Section: Biochemical Properties Of Statinsmentioning
confidence: 99%
“…In contrast, lipophilic statins enter the liver by passive diffusion (Alfaqih et al 2017). The sodium-independent organic anion transporter protein-1B1 (OATP1B1) is exclusively expressed in liver (Menter et al 2011). However, studies on tissue samples revealed decreased levels of OATP1B1 in hepatocellular carcinoma tumor samples compared to normal liver (Cui et al 2003;Zollner et al 2005).…”
Section: Biochemical Properties Of Statinsmentioning
confidence: 99%